PENGGUNAAN MEDIA SALINDIA INTERAKTIF UNTUK MENARIK MINAT BELAJAR SISWA SEKOLAH DASAR DALAM PEMBELAJARAN DARING - Metha E. Br. Simamora; Wiputra Cendana (Universitas Pakuan, 2021)
THE USE OF INTERACTIVE POWERPOINT TO INCREASING ELEMENTARY SCHOOL STUDENTS LEARNING INTEREST IN ONLINE LEARNINGThe purpose of this research is to describe the effectiveness of PowerPoint to engage primary students especially in the online learning setting. Method that have been using for this research was qualitative descriptive with the instruments are lesson plan, observation log, and teacher’s mentor feedback. The result show that the use of PowerPoint was effective to engage students in learning because there are many features that support teacher to teach. The features is use to add pictures, video, and particularly hyperlink features that help user to made nonlinear presentation, so the teacher can design an interactive quizzes. PowerPoint also support students to learn individually at home in this kind of online learning setting. It can be conclude that PowerPoint is effective to engage primary student in online learning. Therefore the researcher suggest that the PowerPoint can be validated by the expert so that it can use for teaching primary students in online learning around Indonesia.